THE SYMBOLISM OF SILENCE AND DEVOTION IN “BLINDING LIGHTS” : A SEMIOTICS ANALYSIS - Abigael Novita Sari; Rawuh Yuda Yuwana (PT Akselerasi Karya Mandiri, 2024)
This study presents a semiotic interpretation of Blinding Lights by The Weeknd, focusing on how the song constructs symbolic representations of emotional states such as loss, loneliness, devotion, and hope. Using the theoretical frameworks of Saussure, Peirce, Barthes, and Yuwana, the analysis reveals the way linguistic and symbolic signs, such as light, darkness, silence, and urban imagery, encode emotional depth within the narrative of romantic longing. The study identifies how these signs interact to form a coherent structure of meaning that resonates with the universal experience of separation and devotion. The findings show that popular music, far beyond entertainment, serves as a space of cultural signification, conveying complex affective messages through semiotic constructs. This research contributes to the growing field of music semiotics and affirms the relevance of contemporary song lyrics as legitimate texts for scholarly analysis.